Does Macroeconomic Condition Matter for Stock Market? Evidence of Indonesia Stock Market Performance for 21 Years - Satria Aji Setiawan (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2020)
The stock markets are becoming an essential and inseparable part of the economies in many countries, including Indonesia. The fact that stock markets indices become one of the indicators to determine the healthiness of country economics showing the importance of the stock market in a country. Whenever the stock market experiences a substantial decline, there is reason to fear that a recession may come. Thus, policymakers and the government have to be aware of this matter. Macroeconomics plays an essential role in economies activities as well as brings an effect to stock market performance. GDP as an indicator of economic growth, inflation that is limiting consumption, interest rate, and exchange rate are selected macroeconomic variables that affect the stock market performance. Using multiple regression analysis, it is known that GDP and inflation contributing to the rise of stock market value, albeit the effect of inflation is not significant. Contrary, interest rate and exchange rate bring a negative impact on the stock market performance, primarily interest rate, which has a significant effect.